Risk Evaluation and Mitigation Strategies: A Focus on Belatacept. (March 2013) - Sam, Teena; Gabardi, Steven; Tichy, Eric M.
Objective: To review the elements and components of the risk evaluation and mitigation strategies (REMS) for the costimulation blocker belatacept and associated implications for health care providers working with transplant recipients. Data Sources and Extraction: The MEDLINE and EMBASE databases (January 1990 to March 2012) were searched by using risk evaluation and mitigation strategies, REMS, belatacept, and organ transplant as search terms (individual organs were also searched). Retrieved articles were supplemented with analysis of information obtained from the Federal Register, the Food and Drug Administration, and the manufacturer of belatacept. Data Synthesis: REMS are risk-management strategies implemented to ensure that a product's benefits outweigh its known safety risks. Although belatacept offers a novel strategy in maintenance immunosuppression and was associated with superior renal function compared with cyclosporine in phase 2 and 3 trials, belatacept is also associated with increased risk of posttransplant lymphoproliferative disorder and central nervous system infections. The Food and Drug Administration required development of a REMS program as part of belatacept's approval process to ensure safe and appropriate use of the medication and optimization of its risk-benefit profile. Conclusion—Elements of the belatacept REMS include a medication guide that must be dispensed with each infusion and a communication plan. In the management of a complex population of patients, it is essential that those who care for transplant recipients, and patients, recognize the implications of potential and known risks of belatacept. The REMS program aims to facilitate careful selection and education of patients and vigilant monitoring.